STANDAR PELAYANAN TERMINAL PENUMPANG TIPE A TIRTONADI SURAKARTA DI PROVINSI JAWA TENGAH - Irenita, Novembria; Ardhya Ekawati, Dian; Tantry, Francis; Parlindungan, Purbanuara; Febriansyah, Rizky (Jurnal Sistem Transportasi & Logistik, 2021)
The terminal is main network knot is a collection of all the route. But the existence of passenger terminal were not yet functioning effectively, this can be seen from the low utilization rate of transportation service terminal by the user. So that the efforts to improve services in terminal. One of the efforts made to improve services in terminal is the performance of service evaluation by standards of service in terminal comprising the services is safety, security, reliability, comfort, convenience and equality . This research was conducted in Tirtonadi Terminal using quantitative method and descriptive research with 355 people of samples. Data were collected through an instrument in form of the question by the model scale liken have tested. The research was analyzed. Using Importance Performance Analysis (IPA) technique. The result’s of the research, first, it was quality of service in Tirtonadi Terminal is 81,41 that was in value of services B with satisfactory category. Secondly, it was quality of service in Tirtonadi Terminal not meet the expectations of users. Thirdly, it was service a top priority for improvement is safety information, internet network facilities, charging comer, waiting room, and arrival and departure schedule with tariff public transportation.